Cognitive development and learning in instructional contexts - Byrnes, James P. (Boston : Allyn and Bacon, 1996)
1. Educational Psychology--Cognition 2. Learning,Psychology of.--Child Psychology--1.Title
Includes bibliographical references and index.
Faulty
Keywords: Educational psychology; Cognition; Learning, Psychology of; Child psychology